Evaluation of an evidence-based practice continuing education course for Canadian Naturopathic Doctors - Monique Aucoin; Genevieve Newton; Matthew Leach; Kieran Cooley (PLoS ONE, 2025)
Background Evidence-based practice (EBP) combines the best available evidence with clinician expertise and patient preference to improve patient outcomes. Recent evidence indicates that Canadian Naturopathic Doctors (NDs) are interested in EBP skill development. The primary objective of the present study was to assess the feasibility and acceptability of a co-designed EBP Continuing Education (CE) course for Canadian NDs. Secondary objectives included assessing changes in EBP skill, use, attitudes, and knowledge. Methods The CE course was evaluated using a pre-post design involving licensed Canadian NDs. The CE course consisted of five weekly, one-hour sessions that were delivered virtually. On course completion, participants reported on their level of satisfaction and provided suggestions for improvement. EBP skill, attitudes and use were assessed using the validated Evidence-Based Practice Attitudes and Utilization Survey. EBP knowledge was objectively assessed using a quiz. Changes in EBP skill, attitudes, use and knowledge were compared between baseline and the end of the course. Use of evidence was reassessed at a 2-month follow up. Results Sixty-one NDs met eligibility criteria. Eighty-nine percent of participants agreed or strongly agreed that they were satisfied with the course. There was a significant increase in self-reported skill and objectively measured EBP knowledge, but no substantive change in EBP attitudes or use of evidence over time. Some participants indicated the level of difficulty was too high while others reported that it could have been more difficult. Participants also wanted more opportunities to practice the skills being taught in the course. Conclusions Delivery of the co-designed EBP CE course was found to be both feasible and acceptable. Preliminary evidence suggests that participation in the course was associated with improvements in EBP knowledge and skill. Participants provided actionable suggestions to improve the course in future iterations.